2014
DOI: 10.1371/journal.pone.0095704
|View full text |Cite
|
Sign up to set email alerts
|

The State-Led Large Scale Public Private Partnership ‘Chiranjeevi Program’ to Increase Access to Institutional Delivery among Poor Women in Gujarat, India: How Has It Done? What Can We Learn?

Abstract: BackgroundMany low-middle income countries have focused on improving access to and quality of obstetric care, as part of promoting a facility based intra-partum care strategy to reduce maternal mortality. The state of Gujarat in India, implements a facility based intra-partum care program through its large for-profit private obstetric sector, under a state-led public-private-partnership, the Chiranjeevi Yojana (CY), under which the state pays accredited private obstetricians to perform deliveries for poor/trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…Our finding of no programme effect on maternal health service coverage is comparable to studies of demand-side financing in India, which used a similar quasi-experimental design to our own (De Costa et al, 2014;Mohanan et al, 2014). However, studies from Bangladesh (Ahmed & Khan, 2011;Nguyen et al, 2012), Pakistan (S. Sohail Agha, 2011) and Uganda (Ekirapa-Kiracho et al, 2011) reported positive effects on antenatal, delivery and postnatal care use.…”
Section: Discussionsupporting
confidence: 83%
“…Our finding of no programme effect on maternal health service coverage is comparable to studies of demand-side financing in India, which used a similar quasi-experimental design to our own (De Costa et al, 2014;Mohanan et al, 2014). However, studies from Bangladesh (Ahmed & Khan, 2011;Nguyen et al, 2012), Pakistan (S. Sohail Agha, 2011) and Uganda (Ekirapa-Kiracho et al, 2011) reported positive effects on antenatal, delivery and postnatal care use.…”
Section: Discussionsupporting
confidence: 83%
“…One example of PPP is the state led Chiranjeevi Yojana (CY) program of Gujarat state in India implemented to full scale in 2007 that used explicit performance-based subsidies to motivate private sector obstetricians to provide institutional delivery services at a defined level of quality and at an affordable cost to disadvantaged women [43]. Similar direct reimbursement to the health providers such as nurse/ANMs in accredited private birthing centers and clinics (preferably with an obstetrician) can be explored for situations when the public sector facilities capacity to provide emergency obstetric care is low [44].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Gujarat corroborated the findings of the present study that, after the introduction of PPP as a reformative measure through the Chiranjeevi Yojana in the healthcare, the institutional birth rose from 40.7% in 2001 to 89.3% in 2010. 21 Another study undertaken in Odisha critically examined the performance of Primary health centres (PHC) under government (PHC-GOV), NGO (PHC-NGO) and corporate (PHC-COR) and found that, there is no significant variation in the breadth and depth of services across all the three models of PHC management. The study further argued that, PHC-GOV had better accessibility, infrastructure, behaviour of doctors and availability of Note: The numbers of treated and controls refer to actual nearest neighbour.…”
Section: Discussionmentioning
confidence: 99%
“…The study was explorative in nature conducted during January to March 2016 in Odishaa high-focused state for its poor maternal health indicators in India. 8,21 Respondents were selected cross-sectionally from three differently-managed i.e. public, private and publicprivate partnership (PPP) health facilities.…”
Section: Methodsmentioning
confidence: 99%